القيم السائدة في قصص الاطفال الكردية - حسين، عبدالعزيز حيدر; فرحان، علي ناصر; علي، غلوم محمد (جامعة بغداد - مركز البحوث التربوية والنفسية, 2015)
يهدف البحث إلى معرفة على القيم السائدة في قصص الأطفال الكردية، والفروق ذات الدلالة الإحصائية بين المجموعات القيمية. وفي الاطار النظري استعرضت تعريفات للقيمة ، كما عرضت مجموعة من الدراسات السابقة واهم النتائج التي توصلت اليها. ولتحقيق أهداف البحث تطلب أجراء تحليل لمحتوى ١٤ قصة من قصص الأطفال الكردية والمترجمة إلى اللغة العربية وفق تصنيف وايت وبعد التأكد من ثبات هذه الأداة توصل الباحث إلى النتائج التالية : حصلت مجموعة القيم المعرفية والقيم الجسمانية على اعلى النسب ، بينما حصلت مجموعة القيم الأخلاقية والعملية والوطنية والقومية على ادنى النسب. كما وجد ان هناك فروق ذات دلالة احصائية بين التكرارات الملاحظة وبين التكرارات المتوقعة في مجاميع القيم الجسمانية والترويحية. ويعتقد الباحثون ان هذه النتيجة جاءت متفقة مع حقيقة ان المعرفة هي الأساس في سلم مستويات البناء المعرفي ، وان كتاب القصص أعطوا أهمية لهذا الجانب. كما ان ورود القيم الجسمانية بهذه المرتبة العالية ينسجم مع طبيعة مرحلة الطفولة التي تمتاز بالنشاط والحوية ، فضلا عن حقيقة أخري تتعلق بالطبيعة الجغرافية للمنطقة الكردية التي تتميز بوعورة جبالها وكثرة وديانها والتي تتطلب طاقة جسمية عالية لمن بعيش لها.
The goal of the research is to identify prevailing values in Kurdish children’s stories, and statistically significant differences between groups. In the theoretical framework, the definitions of values are reviewed. Furthermore, a range of previous studies were offered, with the most important findings. To achieve the goals of this research, an amount of 14 Kurdish children’s must be analyzed. The selected Kurdish children’s stories must be translated to Arabic conform the classification ’White’. After confirming the stability of this tool, the researcher reached the following results: The cognitive and physical values received the highest ratios, while the moral, practical, patriotic and nationalistic values received the lowest. The researcher also found that there are statistically significant differences between repeating the note and expected frequencies in the totals for physical and recreational values. The researchers believe that this result was consistent with the fact that knowledge is the basis of building cognitive levels, and that the writers gave importance to that aspect. Also, physical values at such a high rank are in harmony with the nature of childhood, characterized by activity and vitality. As a addition to another fact, related to the geographical nature of the Kurdish region, which is characterized by the mountains and the valleys, which require high physical energy to survive it.
Keywords: علم النفس التربوي -- قصص الاطفال -- رياض الأطفال